Childhood rosacea. Report of 11 cases. - Chieco, P. (European Journal of Pediatric Dermatology, 2013)
Rosacea is a skin disorder clinically characterized by flushing or persistent erythema, telangiectasias, papules and pustules of the central area of the face. Rosacea is rare in children and mainly characterized by papules and pustules of the central region of the face. Taking into account our eleven cases of childhood rosacea and the literature data, we suggest to eliminate flushing and persistent erythema from the diagnostic criteria of childhood rosacea, both for their rarity in this age and for the greater frequency of a possible source of confusion as constitutional rubeosis of children.